Antimicrobial Resistance Mechanisms and Virulence of Colistin- and Carbapenem-Resistant Acinetobacter baumannii Isolated from a Teaching Hospital in Taiwan - Noor Andryan Ilsan; Yuarn-Jang Lee; Shu-Chen Kuo; I-Hui Lee; Tzu-Wen Huang (Microorganisms, 2021)
Acinetobacter baumannii, a Gram-negative bacterium, is an important nosocomial pathogen. Colistin-resistant A. baumannii is becoming a new concern, since colistin is one of the last-line antibiotics for infections by carbapenem-resistant A. baumannii. From 452 carbapenem-resistant isolates collected in a teaching hospital in Taipei, Taiwan, we identified seven that were resistant to colistin. Carbapenem resistance in these isolates is attributed to the presence of carbapenemase gene blaOXA-23 in their genomes. Colistin resistance is presumably conferred by mutations in the sensor kinase domain of PmrB found in these isolates, which are known to result in modification of colistin target lipid A via the PmrB–PmrA–PmrC signal transduction pathway. Overexpression of pmrC, eptA, and naxD was observed in all seven isolates. Colistin resistance mediated by pmrB mutations has never been reported in Taiwan. One of the seven isolates contained three mutations in lpxD and exhibited an altered lipopolysaccharide profile, which may contribute to its colistin resistance. No significant difference in growth rates was observed between the isolates and the reference strain, suggesting no fitness cost of colistin resistance. Biofilm formation abilities of the isolates were lower than that of the reference. Interestingly, one of the isolates was heteroresistant to colistin. Four of the isolates were significantly more virulent to wax moth larvae than the reference.